Pengaruh Kualitas Implementasi Model Pembelajaran Problem Based Learning dan Discovery Learning Berbantuan Aplikasi Canvas terhadap Prestasi Belajar Mata Pelajaran Desain Grafis Percetakan di SMKN 5 Malang - Alma Syahara Nur Cholidhea; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The learning activities of Printing Graphic Design class XI MM at SMKN 5 Malang are often teacher centered, causing students to be less active, independent, cooperating and having maximum learning achievement. The 2013 curriculum still maintains constructivism-based learning that involves more students than teachers, with suggested learning models including Problem Based Learning (PBL) and Discovery Learning (DL) which can increase activeness, independence, cooperation and learning achievement. This study aims to determine differences in learning achievement between the application of PBL and DL in class XI Multimedia SMKN 5 Malang. This type of research is an experiment using a Pretest-Postest Group Design, using a quantitative approach with a population of class XI Multimedia students of SMKN 5 Malang. Sampling by random sampling obtained a sample of students class XI MM 3 (30 students) as the experimental class 1 and XI MM 4 (30 students) as the experimental class 2. The statistical test consists of normality test using the Shapiro-Wilk method, homogeneity test using the method Lavene's, and the average difference hypothesis test using the Independent Sample T Test, which was carried out at a significance level of 0.05. Hypothesis testing resulted in a significance value of 0.000 with the average value of students in the PBL class being higher than the DL, so it can be concluded that the application of the PBL and DL models affects activeness, cooperation, independence and produces higher PBL learning achievement than the DL model.